ANALISIS PENGARUH GAYA KEPEMIMPINAN DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI PADA PERWAKILAN BKKBN PROVINSI ACEH - Tamlikha Tamlikha; Djonet Santoso; Hedi Heryadi (TheJournalish: Social and Government, 2022)
Abstract: For the realization of employee performance in an organization or institution, of course, it is very much influenced by the leadership. The leader or leader is the highest symbol for an institution that can run the wheel of power. The purpose of this study was to examine and analyze the effect of leadership style and work motivation simultaneously on improving the performance of BKKBN Aceh Province employees, to test and analyze the effect of leadership style on employee performance improvement and to examine and analyze the effect of work motivation on employee performance improvement. The location of this research was conducted at the BKKBN Provisni Aceh Office, with a total of 56 respondents. Methods of data analysis in this study using quantitative analysis methods and qualitative analysis methods. Quantitative analysis in this study uses multiple linear regression, namely to determine the relationship (association) between two variables, namely variable X (independent) and variable Y (dependent). The results of the research jointly prove that leadership style and work motivation together have an influence on improving the performance of the employees of the Aceh Provincial BKKBN Representative Office, this is evidenced by the Fcount value of 35.839 and Ftable of 3.171, thus Fcount> Ftable, so that the hypothesis the proposed alternative (Ha) is accepted and rejects the null hypothesis (Ho). While the results of the research that partially the leadership style will have an impact on improving the performance of the employees of the Aceh Provincial BKKBN Representative Office, this is evidenced by the tcount value of 6.546, so that the proposed alternative hypothesis (Ha) is accepted and rejects the null hypothesis (Ho). As for the work motivation variable also has an impact on improving the performance of the employees of the Aceh Provincial BKKBN Representative Office, the t-count value is 2.973, so the proposed alternative hypothesis (Ha) is accepted and rejects the null hypothesis (Ho).